Exploring Library Activities, Learning Spaces, and Challenges Encountered Towards the Establishment of a Learning Commons - Beneyat-Dulagan, Maryjul T.; Cabonero, David A. (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2023)
Objectives – This study was conducted to determine the library activities, preferred learning spaces, and challenges encountered by the students of Mountain Province State Polytechnic College (MPSPC) Library, Philippines. Specifically, it sought to answer the following problems: 1) What are the library activities of MPSPC students?; 2) What are the preferred learning spaces in terms of a) physical environment and b) virtual environment?; and 3) What are the challenges associated with library learning activities encountered by the MPSPC students? The study then will be used to explore the feasibility of proposing a learning commons.Methods – This study used a descriptive research method to determine the library activities, learning spaces, and challenges encountered by MPSPC students in the Philippines. It made use of a researcher-made survey questionnaire. Problem statement number 1 dealt with the library activities of MPSPC students. Problem statement number 2 dealt with the preferred learning spaces. Data were gathered from 500 graduate and undergraduate students from a total of 3,015 enrolled during the first semester of the SY 2019-2020 using a purposive random sampling technique. Descriptive statistics such as frequency, percentage, and rank were used.Results – The most frequent library learning activities performed by the MPSPC students were doing assignments, using reference books, searching/browsing printed materials, reviewing notes, and writing. Students’ least frequent library activities were surfing the web, using the computer, using e-resources, eating while reading/writing, and sleeping. The most preferred physical learning spaces were a makerspace, group study spaces, quiet study rooms, and individual study spaces (individual study carrels), while the most preferred virtual learning spaces were computer workstations, interactive learning spaces, video viewing stations, and internet cafés. The overall challenges encountered by MPSPC students were insufficient learning spaces, poor internet connection, inability to find documents or books needed, lack of reading area, lack of printing or photocopying service, lack of professional books, and lack of e-resources. The least challenges encountered by MPSPC students included very high library fees, poor ventilation, poor lighting facility in the designated area, uncomfortable furniture, and lack of staff’s kindness.Conclusion – The MPSPC students perform various educationally purposeful library activities, which are generally engaging and support the library's mission. Students vary in their needs of physical and virtual learning environments. Both of these learning spaces are in demand among students, which are the key components of the learning commons. Also, they specified the need for adequate learning spaces to support their various library learning activities. The findings serve as the basis for crafting a project proposal to establish a learning commons tailored to MPSPC students’ library activities and preferred learning spaces, with consideration for the challenges encountered by students, to support their learning and academic success.